Tematik Dalam Kumpulan Puisi “Melipat Jarak” Karya Sapardi Djoko Damono - Latifa, Hapsyah; Nasution, M. Ismail (Universitas Negeri Padang, 2024)
The subject of this research is the themes contained in the poetry collection Melipat Jarak by Sapardi Djoko Damono. The approach used in this research is an objective approach. This type of research is literary research using descriptive method. The data used in this research are words, phrases and clauses and sentences that contain structures and themes. After analyzing, the results show that the themes in Sapardi Djoko Damono's poems are found physical, organic, social, egoic, and divine themes. Sapardi Djoko Damono's poems have various themes so that his poems are interesting because they do not only carry one theme.